2021
DOI: 10.7759/cureus.16192
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Endogenous Streptococcal Endophthalmitis in the Critical Care Setting

Abstract: We report a rare case of orbital cellulitis and endogenous endophthalmitis, sepsis, meningitis with a brain abscess and a septic knee secondary to Streptococcus pneumonia.The problems of diagnosis, utility of CT and MRI scanning in the intensive care setting is discussed. The patient was admitted in an obtundated state to the ICU, was noted to have sepsis with blood culture positivity for S pneumoniae. She was noted to have meningitis, a septic knee, a brain abscess and conjunctival injection. CT and MRI scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The clams that would have a greater feeding rate would be able to filter more food from the environment, leading to an increased rate of survivability in their environment. The mechanism of filter feeding mainly depends on the spacing of the gills in the clams [8,[11][12][13][14][15]. The two main sources of food for C. Fluminea in this experiment were algae and E. coli.…”
Section: Discussionmentioning
confidence: 87%
“…The clams that would have a greater feeding rate would be able to filter more food from the environment, leading to an increased rate of survivability in their environment. The mechanism of filter feeding mainly depends on the spacing of the gills in the clams [8,[11][12][13][14][15]. The two main sources of food for C. Fluminea in this experiment were algae and E. coli.…”
Section: Discussionmentioning
confidence: 87%
“…In this investigation, the authors attempt to develop an AI software that can be utilized to diagnose cases where patients have exudative or non-exudative macular degeneration in either their left eye, their right eye, or both eyes. Our investigation builds upon previous studies that have demonstrated how AI software can accurately diagnose macular degeneration within a patient [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 87%
“…Maybe future research can be conducted using artificial intelligence to address some of the issues with this drug [17]. Additionally, further research could be done to investigate chemical and physical forces in the body that could help understand more about the pharmacodynamics and the pharmacokinetics of the body [18][19][20]. These limitations need to be addressed in further research to improve the widespread use of the drug.…”
Section: Research Articlementioning
confidence: 99%